Protective effects of Origanum majorana L. against Neurodegeneration: Fingerprinting, Isolation and In vivo Glycine Receptors Behavioral Model - Karim M. Raafat; Hasan Jassar; Maha Aboul-Ela; Abdalla El-Lakany (International Journal of Phytomedicine, 2013)
Extracts from Origanum majorana L. are used in Asia and Africa as sedatives and neurotonics. Few studies done to explore the active chemical constituents responsible for this apparent contrast. The inhibitory glycine receptors (GlyRs) are key mediators of synaptic signaling in spinal cord, brain stem, and higher central nervous system regions. Neurodegeneration may cause alteration of the GlyRs causing strychnine-like convulsions and stiffness. Here, modulation of GlyRs in-vivo was studied in a mouse model of strychnine toxicity. Total phenolics in Egyptian marjoram (Mj-eg) and Lebanese marjoram(Mj-lb) were calculated and fingerprinted. The Mj-eg and Mj-lb ethanolic extracts revealed to be potent modulators to GlyR; with potential anticonvulsant properties in low doses. Chlorogenic acid (CGA), p-coumaric acid (pCA) and p-hydroxy benzoic acid (pHBA) were detected in the active fractions via column chromatography and RP-HPLC fractionation. The active fraction phenolics at harmless low doses, showed anticonvulsant activity by reversing strychnine toxicity in mice. By applying Berenbaum isoblographic method, we confirmed that at low concentrations the protective effects of CGA and pCA on strychnine toxicity are synergistic. It could be concluded that both marjoram and active phenolics could be used as sedatives in low doses and as neurotonics in high doses. In order to fight against neurodegenerative diseases is to improve body antioxidant, marjoram provided to be good sources for antioxidant potential. In brief, the marjoram phenolics, especially CGA, pCA and pHBA, suggested to be novel GlyR modulators, good phytotherapy, pharmacological tool and a dose sensitive drug to treat convulsions, stiffness and neurodegenerative disorders.